Penggunaan Aplikasi Zoom Cloud Meeting pada Mata Kuliah Mekanika dan Termostatistika saat Pandemi COVID-19 - Dedi Riyan Rizaldi; Ziadatul Fatimah (Universitas Hamzanwadi, 2020)
The purpose of writing this article is to explain the application of online based learning using the Zoom Cloud Mettng application during the COVID-19 pandemic. The writing of this article uses a qualitative method of literature review by collecting data in the form of secondary data obtained from various sources such as articles, notes, or other scientific sources. The data collected is then analyzed inductively. Based on the literature review, data analysis, and discussion, it can be concluded that the Zoom Cloud Metting application is an effective medium used in the learning process during the COVID-19 pandemic because it is able to facilitate educators and learning to be able to interact while continuing to prioritize health protocols during the pandemic COVID-19, namely Physical Distancing or maintaining distance.DOI: 10.29408/kpj.v4i2.2237